2010
DOI: 10.1137/080739379
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Computation and the Evaluation of Tensor Networks

Abstract: We present a quantum algorithm that additively approximates the value of a tensor network to a certain scale. When combined with existing results, this provides a complete problem for quantum computation. The result is a simple new way of looking at quantum computation in which unitary gates are replaced by tensors and time is replaced by the order in which the tensornetwork is "swallowed". We use this result to derive new quantum algorithms that approximate the partition function of a variety of classical sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 42 publications
0
84
0
Order By: Relevance
“…We will now show how this worry can be circumvented; we can efficiently measure Tr(W x,z ρ) up to an additive approximation. The protocol that we will follow is largely inspired by studies of the evaluation of tensor networks on a quantum computer [30] which proved particularly useful for calculating partition functions in classical statistical mechanics. Related problems also arose in [31].…”
Section: A Implementing the Entanglement Witnessesmentioning
confidence: 99%
“…We will now show how this worry can be circumvented; we can efficiently measure Tr(W x,z ρ) up to an additive approximation. The protocol that we will follow is largely inspired by studies of the evaluation of tensor networks on a quantum computer [30] which proved particularly useful for calculating partition functions in classical statistical mechanics. Related problems also arose in [31].…”
Section: A Implementing the Entanglement Witnessesmentioning
confidence: 99%
“…Whilst algorithms which can speed up tensor network contractions by optimising the bubbling used [3][4][5], as discusssed above, the underlying computational problem is NP-complete [6,7] Even ignoring the specific bubbling used, the complexity of the overall contraction procedure can also be shown to be prohibitive in general. Consider a network made from the binary tensors e and n. The value of e is 1 if and only if all indices are identical, and zero otherwise, whilst n has value 1 if and only if all legs differ and 0 otherwise.…”
Section: Computational Complexitymentioning
confidence: 99%
“…There it was found that the number Fourier components needed to be sampled scales polynomially with the lattice size, but in order to obtain a mulitplicative approximation of the partition function, the requisite accuracy of estimation of each coefficient scaled exponentially with the system size. An algorithm, based on using a quantum computer to contract tensor networks yields similar approximation scales [3]. Even preparing a quantum state which coherently encodes a classical thermal state of an Ising appears to be difficult, e.g.…”
Section: Partition Functionsmentioning
confidence: 99%
“…During the last ten years, significant efforts have been devoted to investigating whether quantum mechanics could help in this respect. Various methods, all involving the superposition principle, have been proposed to compute the Jones polynomial at particular values of its variable [1], partition functions of classical statistical models [2][3][4], the Tutte polynomial [5], or more generally to contract tensor networks [3].…”
Section: Introductionmentioning
confidence: 99%